(untitled) (Journal of Dhaka Medical College, 2011)
Background: Menstrual regulation (MR) is the abortion method in Bangladesh, majority of unwanted pregnancies are nevertheless induced by unskilled persons using different abortifacients. Now-a-days, in Bangladesh, the women of rural areas have found such an alternative in ’tablet misoprostol’ which is introduced to them by the drug sellers, rural health service providers, and non-technical hospital staffs. Objectives: The objective of this study was to investigate the experience, achievement and satisfaction of clients with acceptability and safety of misoprostol. Methods: This observational study was carried out on all the patients attending outpatient as well as inpatient departments with a history of abortion at Chakaria Upazilla Health Complex, Cox’s Bazar from October, 2009 to April, 2010. But the patients who had a history of misoprostol induced abortion only were treated as the sample. Results: Out of the 66 abortion patients (study population), 43 were the sample (65.15%). Women took vaginal bleeding as achievement for termination of pregnancy, no mater whether it was complete or partial. Side effects of the drugs e.g. pyrexia, shivering, vomiting and cramp were short lasting and were within tolerance level, and thus induced women to accept the procedure gladly. All of them accepted it for future use (100%) and would recommend the procedure for friends and family (100%). Conclusion: The present study found an off-label use of misoprostol by the women themselves as abortifacients in a poor rural setting in Bangladesh. The women used the drug as they found it safe, cost effective and efficacious, and a self applicable home method. Its availability in open market (as an antiulcer drug) also facilitates its use. Key Words: Misoprostol; termination of pregnancy; induced abortion; rural women. DOI: 10.3329/jdmc.v19i2.7079 J Dhaka Med Coll. 2010; 19(2) : 109-114